2011
DOI: 10.1111/j.1440-1827.2011.02759.x
|View full text |Cite
|
Sign up to set email alerts
|

Case report of mammary analog secretory carcinoma of the parotid gland

Abstract: Mammary Analog Secretory Carcinoma (MASC) is a new entity of malignant salivary gland tumors that morphologically resembles mammary secretory carcinoma and carries the identical ETV6-NTRK3 fusion gene. We report our first case of MASC in Japan occurring in the parotid gland of a 37-year-old female patient with a t (12; 15) (p13; q25) translocation. Histologically, the tumor was composed of monomorphic cuboidal cells with low-grade vesicular nuclei and pale eosinophilic cytoplasm, and formed microcystic and tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 8 publications
1
52
0
Order By: Relevance
“…[3][4][5][6][7] Immunohistochemistry studies may be useful in the differential diagnosis between mammary analog secretary carcinoma and its mimics. The former are reactive for S-100 protein and mammaglobin in the vast majority of cases, 1,[3][4][5][6]8 however, these two markers, S-100 in particular, are likewise found to be occasionally positive in other adenocarcinomas of salivary gland origin. Acinic cell carcinomas tend to be negative for mammaglobin, but can rarely demonstrate immunoreactivity for S-100.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] Immunohistochemistry studies may be useful in the differential diagnosis between mammary analog secretary carcinoma and its mimics. The former are reactive for S-100 protein and mammaglobin in the vast majority of cases, 1,[3][4][5][6]8 however, these two markers, S-100 in particular, are likewise found to be occasionally positive in other adenocarcinomas of salivary gland origin. Acinic cell carcinomas tend to be negative for mammaglobin, but can rarely demonstrate immunoreactivity for S-100.…”
mentioning
confidence: 99%
“…Moreover, 8 new cases of MASC have been documented as case reports within last two years [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the authors found that these salivary gland tumors shared the immunophenotype and, remarkably, the characteristic ETV6-NTRK3 translocation of secretory breast carcinoma, and they accordingly designated them ''mammary analogue secretory carcinomas'' (MASCs). Since the initial description, MASC has been increasingly recognized, with 70 additional reported cases [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%